Contrasting patterns from two invasion fronts suggest a niche shift of an invasive predator of native bees - Maria João Verdasca; Luisa Carvalheiro; Jesus Aguirre Gutierrez; José Pedro Granadeiro; Quentin Rome; Sebastien J. Puechmaille; Rui Rebelo; Hugo Rebelo (PeerJ, 2022)
Background The accuracy of predictions of invasive species ranges is dependent on niche similarity between invasive and native populations and on our ability to identify the niche characteristics. With this work we aimed to compare the niche dynamics of two genetically related invasive populations of Vespa velutina (an effective predator of honeybees and wild pollinators), in two distinct climatic regions, one in central Europe and another one in the north-western Iberian Peninsula, and hence to identify uninvaded regions susceptible to invasion. Methods Niche dynamics and shifts of V. velutina were assessed by comparing the environmental niches of the native and of the two invasive populations, using climatic, topographic and land use variables. We also ran reciprocal distribution models using different algorithms and records from both native and invasive ranges to compare model predictions and estimate which regions are at a greater risk of being invaded. Results An apparent niche shift was detected in the population of the NW of Iberian Peninsula, where the species is living under environmental conditions different from the native niche. In central Europe, large suitable areas remain unoccupied. The fact that both invasive populations are well established, despite occupying environmentally distinct regions indicates that V. velutina has a high ability to successfully invade different environmental envelopes from those existing in its native range. For example, in north-western Iberian Peninsula the species is now thriving out of its native niche limits. Moreover, the large extent of still unoccupied environmental space with similar conditions to those used by the species in its native range suggests that there is still a large area of central and eastern Europe that can be potentially invaded by the species.